"This is the destiny, darling": Relational acts in Chinese management responses to online consumer reviews. (April 2019) - Feng, Wei; Ren, Wei
Highlights: The paper investigated relational acts in Chinese management responses to online consumer reviews. The distribution of relational acts was also investigated against the positive or negative nature of the comments. The analyses resulted in 14 relational acts. Review valence (positive vs. negative) played a critical role in the retailer's employment of relational acts. Abstract: Online consumer reviews pose a unique challenge yet meanwhile provide an extraordinary opportunity to the rapport management of retailers. Nonetheless, there is a scarcity of research that has explored pragmatic strategies and rapport management in responses to such reviews. In view of this gap, this study reports on an examination of relational acts in Chinese management responses to online consumer reviews, based on an extensive analysis of 220 items of management responses collected from two leading Chinese e-commerce websites. The study identified 14 relational acts and results showed that despite similarities, review valence (positive vs. negative) played a critical role in the retailer's employment of relational acts for the rapport management purpose. The findings and practical implications furnish timely and much-needed evidence to the pragmatic investigation into the genre of management response, particularly in languages other than English.